Evaluating the Three-Phase Computer Literacy Training Program for Alternative Learning System Students: A Comprehensive Analysis of the Pagpabakud kang Kinaaram Paagi sa Teknolohiya Initiative - Española Jr, Alberto M.; Eraga, Maricel A.; Yumen, Maria Odessa Y.; Yumen, Jovie J. (Transpublika Publisher, 2025)
This comprehensive study evaluates the effectiveness and impact of the three-phase